Review Determinasi Sistem Informasi Manajemen: Database, Komputer dan Software - Juniwati, Maria; Tri Cahyani, Nurfajriati; Ridwantoro, Viky; Arief Hidayat, Asharudin (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
Management information systems have a close relationship with various components in the process of creating information systems that meet their needs. The proper implementation of these components is crucial because inaccurate, insufficiently detailed, untimely, and irrelevant information can lead to errors in the company's decision-making process. Therefore, a deep understanding of the components and management information systems, especially in terms of Databases, computers, and Software , is essential in order to generate valuable, effective, and high-quality information for the company. The purpose of this article is to develop hypotheses regarding the interplay between variables that can be used in further research. The findings of this study are as follows: 1) Databases have an influence on Management Information Systems; 2) Computers have an influence on Management Information Systems; and 3) Software has an influence on Management Information Systems.